Anglicisms in Women’s Press Between the 19th and 20th Centuries: “La Moda Elegante” - Amador, María Vázquez (2023)
This paper intends to analyze the anglicisms found in the fashion magazine La Moda Elegante (1860-1927). To do so, these words were extracted, and categorized according to their thematic areas, formal typology, frequency of use and first appearance. Previous editions of the dictionaries of the Royal Spanish Academy and the current edition of the Diccionario de la Lengua were consulted. Eighty-eight anglicisms related to fashion, social chronicles, sports and other topics were identified. They were mostly non-adapted and infrequent voices. A high percentage of these anglicisms were included in the dictionaries, and most of them are still valid in the current edition. These data show that they were novel concepts related to new realities which have been incorporated into our language.